Prevalence of human papillomavirus in esophageal carcinoma in Tangshan, China - Mehryar, Mohammadreza Mohammadzad (World J Gastroenterol, 2015)
AIM: To study the prevalence of human papillomavirus (HPV) in esophageal carcinoma in Tangshan, China, a high-incidence area. METHODS: Formalin-fixed, paraffin-embedded tissue specimens from 198 patients who were pathologically diagnosed with esophageal squamous cell carcinoma from 2011 to 2013 were obtained from a pathology department in Tangshan. DNA was extracted from all 198 specimens to detect HPV by polymerase chain reaction (PCR). β-globin PCR was performed to check the quality of the DNA extraction procedure. PCR was performed to detect a wide range of HPV types, and type-specific PCR was performed to detect HPV types 16 and 18. Negative and positive controls were used for HPV 16 and 18 detection. RESULTS: The DNA extraction method in this study appeared to be more effective than other previously reported methods. After DNA extraction, more than 98% of the tissue specimens had an acceptable result in the DNA qualification test (β-globin PCR). The overall prevalence of HPV in tumor tissues by GP6+/GP5+ PCR was 79.79%, and the prevalence of HPV types 16 and 18 was 40.40% and 47.47%, respectively. PCR demonstrated the presence of HPV, and direct sequencing confirmed the HPV genotypes. All HPV-positive PCR products were checked by DNA sequence analysis using DNAman and compared with the known HPV sequences listed in the Basic Local Alignment Search Tool database to evaluate the HPV types. This analysis confirmed the presence of HPV types 16 and 18. CONCLUSION: DNA of high-risk HPV types 16 and 18 is present in esophageal tumors, implicating HPV as a possible etiologic factor for esophageal squamous cell carcinoma.